Transição ordem-desordem da matéria de vórtices em supercondutores detectada através do terceiro harmônico da suscetibilidade AC - Oliveira, Ana Augusta Mendonça de (Universidade Federal de São Carlos, 2008)
Although a vortex state, in type II superconductors, has been anticipated more than 50 years ago, a great deal of theoretical and experimental efforts has still been done in an attempt to investigate how the dynamics of these structures depends on external excitations and on the inherent properties of the underlying superconducting material, such as inhomogeneities (Static Disorder). In this work, we studied, in granular samples and polycrystalline 1−2, the effects of different types and quantities of static disorder on the dynamic behaviour of the vortices. The analysis of such effects, using an extremely sensitive experimental technique, the Third Harmonic of the AC Susceptibility, was the main motivation for this research. Conducting a systematic investigation of the third harmonic, we have established reliable and reproducible experimental procedures to determine changes between different regimes of Vortex Matter (VM). In particular, we distinguished a regime of linear response and, other, of non-linear response, which were identified as representative of disordered and ordered phases of VM, respectively. As a consequence, a new frontier, delimitating these phases, was incorporated to the magnetic diagrams of the studied systems, denominated as Order Disorder Threshold (OD). We also analyzed the evolution of that OD threshold with the addition of inhomogeneities, as well as the format of the contour. With regard to form, two distinct behaviours were revealed and, consequently, interpreted as resulting from a competition between different types of disorder static and dynamic present in the materials. The most intriguing result reported, concerns to the anticipation, in the high temperature/low field region, of the OD limit, which we associated to a Thermally Induced Depinning Transition. In addition, we compared the OD lines with the Irreversibility Line (LI), obtained through magnetization measurements for some of the analyzed samples, pointing out the differences and similarities between them. Measurements of electrical transport and magnetic relaxation were also performed. The results derived from them contributed significantly to the study accomplished, leading to a broader view of the dynamic behaviour of vortices in the vicinity of this newly determined OD threshold.
Keywords: Matéria de vórtices; Susceptibilidade magnética; Supercondutores; Transição ordem-desordem; CIENCIAS EXATAS E DA TERRA::FISICA